(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Two-wheelers, which are very inexpensive compared to other forms of transportation, arewidely used across India. Hybrid electric vehicles use an electric rear wheel motor, battery, plus controlsystem in conjunction with a conventional internal combustion engine to drastically reduce fuelconsumption and harmful pollutants. At low speeds, when combustion engines are at their leastefficient, a hybrid electric car may get by on electricity from the battery alone.Though they are also ahuge source of pollution, accounting for about 20 of overall pollution (which is 10 greater thanautomobile pollution) and increasing the demand and supply gap of oil, which was 6 million barrels perday in 2020 and is expected to climb by 14.4 million barrels. All of this may be avoided by simplyreplacing internal combustion engine cars with pure electric or hybrid electric two-wheelers. Electricmotors assist engines accelerate, drive great distances, and climb hills. This allows a smaller, morepowerful engine. So, it’s excellent for growing cities with considerable traffic. This article addresses theconcept of simulating a HEV two-wheeler utilising power split to exchange power between the IC engineand motor and deliver a balanced output to the controller.